Sociolinguistics in the Interaction of Typical Children with Children with Special Needs in Inclusive ECCE - Diana Romdhoningsih; Maulida Nur; Rina Andriani (Edunesia : Jurnal Ilmiah Pendidikan, 2026)
This study examines social interaction between typically developing children and children with special needs (CWSN) in inclusive kindergarten settings, focusing on sociolinguistic aspects. The Research is urgent because understanding early communicative practices helps foster healthy social relationships; typical children's limited knowledge of how to interact with CWSN can lead to misunderstandings, exclusion, or barriers to learning. The study identifies and analyses language use, communication strategies, and social factors influencing these interactions. A descriptive qualitative approach was employed using participatory observation and in-depth interviews with teachers and parents. Data were analyzedanalyzed by examining linguistic and social patterns observed during natural interactions. Findings indicate that typical children predominantly employ three strategies: neutral responses, sympathetic responses, and spontaneous responses, which suggest a tendency toward social acceptance of CWSN and positive contributions to inclusion. However, teacher and parent facilitation remains essential to develop more reciprocal and interactive communication. The study recommends teacher training and parental involvement to strengthen inclusive communicative practices to support inclusive learning and development.